Elite education and education for social progression - Ismail, Nik Ahmad Hisham; Rahath House, Yousef (Institut Terjemahan dan Buku Malaysia, 2016)
Elites and their roles in the progression for the nation especially in the social aspect.Education is the best vehicle and mechanism for elites to function in a society. The paper studies the effect of their roles in education and nation's development.